KEBIJAKAN HUKUM PIDANA TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA DITINJAU DARI UNDANG-UNDANG NO. 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Elyna Simanjuntak; Syafruddin Kalo; Marlina Marlina; Edy Ikhsan (Universitas Sumatera Utara, 2018)
ABSTRACT The policy in the system of criminal justice is the realization of the regulation in providing “legal certainty” in settling the conflict among children. Law is intentionally cut down to become legal provisions so that the law enforcement does not have the authority to make a policy; they are forced to act in settling the conflict among children. If there is misunderstanding in this legal certainty, it will bring about new conflict since “blinders” are usually used in implementing the law. Judicial power can be used when the opinion of law enforcement is uncertain. Coordination and communication in providing the children’s rights will be the problems in each institution since the commitment for coordinating their interest is not a new thing. The attempt to change children’s characters and behavior will be worse if the support for their facility and infrastructure is far from what has been expected. Public participation needs support from other elements in maximizing the achievement of the system of criminal justice so that the settlement of confilct among children is not included in formal domain. Support from neighborhood is needed to find the solution for improving comfort which is not based on revenge. Keywords : Criminal Law Policy, Children as Perpetrators, Children’s Criminal Justice